The influence of perceive teacher support on high school students’ learning engagement in China - Yang, Liu; Lian, Lim Hooi (Institute of Advanced Engineering and Science, 2025)
This study explores the influence of perceived teacher support on learning engagement and the mediating role played by psychological capital of senior high school students. There were 572 Chinese senior high school students from Inner Mongolia Autonomous Region in China completed a ranger of self-report questionnaires. The results of this study showed that perceived teacher support was significantly and positively related to learning engagement of senior high school students, and positively correlated with their psychological capital which consists of four dimensions: hope, self-efficacy, optimism, and resilience. The psychological capital was significantly and positively associated with learning engagement among senior high school students and mediated the relationships between perceived teacher support and learning engagement.